2013
DOI: 10.1142/s1793604712500531
|View full text |Cite
|
Sign up to set email alerts
|

DIFFERENCES IN CYTOCOMPATIBILITY BETWEEN MWCNTs AND CARBOXYLIC FUNCTIONALIZED MWCNTs

Abstract: Influence of carboxylic functionalization on the cytocompatibility of multiwalled carbon nanotubes (MWCNTs) was investigated in this work. Water contact angle assay showed that the surface of MWCNTs-containing carboxyl (MWCNTs-COOH) became much more hydrophilic compared with pure MWCNTs. In cell-adhesion assays, two cell lines, mouse fibroblast cells (L929) and human umbilical vein endothelial cells (EAHY926) were used to assess the cytocompatibility of materials. The MWCNTs-COOH displayed the improved cell pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…These studies were conducted on neuronal cells [ 11 , 13 ], osteoblasts [ 12 ], and fibroblasts [ 15 ] from human and rat sources. When the MWCNTs were functionalized, the presence of COOH groups enhances cell proliferation, viability, and adhesion due to the -COOH groups rendering the surface hydrophilic and wettable [ 14 ]. Carboxyl functionalized CNTs (CNT–COOH) have been used as an effective template to chemically synthesize HAp [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies were conducted on neuronal cells [ 11 , 13 ], osteoblasts [ 12 ], and fibroblasts [ 15 ] from human and rat sources. When the MWCNTs were functionalized, the presence of COOH groups enhances cell proliferation, viability, and adhesion due to the -COOH groups rendering the surface hydrophilic and wettable [ 14 ]. Carboxyl functionalized CNTs (CNT–COOH) have been used as an effective template to chemically synthesize HAp [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…As discussed earlier, COOH group promotes matrix mineralization. The presence of -COOH groups likely increased differentiation on day 7 [ 14 ] and matrix mineralization after day 28 due to increased hydrophilicity, surface wettability of MWCNTs and facilitating mineral matrix deposition [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous investigation demonstrated that the anticoagulation of MWCNTs was greatly influenced by surface functional groups. In our previous work, we focused on cell and blood compatibility of MWCNTs by different functional groups [ 16 - 20 ]. The improved anticoagulation was observed in COOH + implantation-MWCNTs when compared with pristine MWCNTs [ 13 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we focused on cell and blood compatibility of MWCNTs by different functional groups [ 16 - 20 ]. The improved anticoagulation was observed in COOH + implantation-MWCNTs when compared with pristine MWCNTs [ 13 , 16 ]. The method of COOH + implantation introduced functional carboxyl groups into the surfaces of materials.…”
Section: Introductionmentioning
confidence: 99%